Meningkatkan Indeks Kewirausahaan dan Talent Marketing Dimasa Pandemi Covid 19 - Zunaidah, Farida Nurlaila; Permana, Erwin Putera; Saidah, Karimatus; Primasatya, Nurita; Santi, Novi Nitya; Zaman, Wahid Ibnu; Wenda, Dhian Dwi Nur; Basori, Muhamad (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this community service activity is to hold marketing seminars to motivate and broaden MSME business owners to market their products through online marketing in order to restore the economy after the Covid-19 pandemic. The method in this community service activity is to conduct a field survey and analysis of needs related to the problems faced as well as survey questionnaires to seminar participants. The result of this marketing seminar activity is that most of the respondents have other businesses besides farming, some of which are engaged in the MSME sector. There are respondents who already have experience with online marketing, even though it is limited to whatsapp status, while others still do not have experience. The respondents were very interested in being taught and assisted in trying online marketing strategies. The respondents' impression of this marketing seminar was very good because the speakers who presented the material and provided assistance were not long-winded and easy to understand.